Good-Life Concepts of Moral Value in Robin Hood Movie (Language Circle: Journal of Language and Literature, 2021)
The study aims to know good-life concepts of moral value in Robin Hood movie. This research used qualitative approach. The researcher found that five moral principles are tolerance, belief, kind-hearted, integrity, and responsibility. In this movie, good-live concepts of moral value are tolerance for human relationships with Heaven, belief is entrusting everything to God's power, kind‐hearted is honesty in this movie that the hero succeeded in winning people's hearts by his supporting honesty, integrity is like finding a valuable gem, and responsibility portrayed feels responsible for defense, reminding people of responsibility to protect their position in everywhere.